Role of Dentists during Mass Disasters: A Review - Kiran Vallamchetla; Kotya N Maloth; Vani Chappidi; Stuti Goyal; Sridevi Ugrappa; Srikanth Kodangal (Wolters Kluwer Medknow Publications, 2017)
Mass disasters cause damage, ecological disruption, and loss of human life on a massive scale. The reasons for these ranges from natural causes such as volcanic eruptions and earthquakes to secondary human causes like wars. Such massive disruption of life demands help from people belonging to various sectors of healthcare, providing pre-identified, structured, and systematic aid to the victims of the disaster. This review article highlights the role of a dentist in such massive disasters. The dentist not only provides first aid to the victims but also aids in the identification of human remains.